2022
DOI: 10.1021/acsnano.1c09505
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Ultrasound-Triggered and Hypoxia-Sensitive Nanoprodrug for Cascade Amplification of Sonochemotherapy

Abstract: Hypoxia, the typical and conspicuous characteristic of most solid tumors, worsens the tumor invasiveness and metastasis. Here, we engineered a sequential ultrasound (US)/hypoxia-sensitive sonochemotherapeutic nanoprodrug by initially synthesizing the hypoxia-activated azo bond-containing camptothecin (CPT) prodrug (CPT2-Azo) and then immobilizing it into the mesopores of sonosensitizer-integrated metal organic frameworks (MOF NPs). Upon entering the hypoxic tumor microenvironment (TME), the structure of CPT2-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 52 publications
0
56
0
Order By: Relevance
“…The antitumor activity of LSCaFPCe6 nanodrugs was initially investigated at a cellular level using the cell‐counting kit‐8 (CCK‐8) assay. [ 12 ] To demonstrate cell biocompatibility, the THLE‐3 and 293T cells were treated with different nanomaterials at different doses ( Figure A and Figure S13, Supporting Information). The cell survival rate was above 70% even after 48 h of co‐incubation with LSCaFPCe6 at a high concentration of 160 µg mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The antitumor activity of LSCaFPCe6 nanodrugs was initially investigated at a cellular level using the cell‐counting kit‐8 (CCK‐8) assay. [ 12 ] To demonstrate cell biocompatibility, the THLE‐3 and 293T cells were treated with different nanomaterials at different doses ( Figure A and Figure S13, Supporting Information). The cell survival rate was above 70% even after 48 h of co‐incubation with LSCaFPCe6 at a high concentration of 160 µg mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The fast development of novel minimally invasive or noninvasive therapeutic modalities has been considered as one of as more promising SDT candidates due to their well-defined molecular structures achieved by controlled synthetic modification and excellent biocompatibility. [18,19] At present, various organic sonosensitizers have been adopted for SDT, including porphyrin and their derivatives, [20][21][22][23][24] xanthenes, [25][26][27][28] some anticancer drugs, [29][30][31] and other small-molecule agents such as hypocrellin B, indocyanine green and IR780. [32][33][34][35] However, most organic sonosensitizers are derived from photosensitizers, and their potential phototoxicity issues hinder their further clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…17 Besides, hypoxia results in an elevated level of regulatory transcription factors like hypoxia inducible factor 1α (HIF-1α) that plays a prominent part in tumorigenesis, angiogenesis, and resistance to therapy. 18,19 According to the reports, overexpression of HIF-1α exists in the majority of human cancers and is related to bad prognosis of patients, 20 which makes HIF-1α a valuable target for developing new anticancer drugs. At present, many studies have reported optimizing the materials themselves to improve the therapeutic efficiency by supplementing oxygen at the lesion site or aiming at the characteristics of the hypoxic microenvironment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Generally, owing to the consumption of O 2 during PDT, tumor hypoxia is further aggravated, which leads to PDT resistance in the necrotic and hypoxic areas of solid tumors . Besides, hypoxia results in an elevated level of regulatory transcription factors like hypoxia inducible factor 1α (HIF-1α) that plays a prominent part in tumorigenesis, angiogenesis, and resistance to therapy. , According to the reports, overexpression of HIF-1α exists in the majority of human cancers and is related to bad prognosis of patients, which makes HIF-1α a valuable target for developing new anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%